WOMEN’S PERSONALITY DEVELOPMENT IN SANDRA CISNEROS’ THE HOUSE ON MANGO STREET - Welen Friade Sinaga; Pioro Benevolent Lariesto; Putri Helentina Marpaung (LPPM Universitas Katolik Santo Thomas Medan, 2025)
The development of women’s personality is an important and relevant topic, particularly in the context of patriarchal cultures that continue to influence the lives of many women. This study examines the family and social factors that contribute to the development of women's personalities. Employing a narrative qualitative methodology, the primary data is drawn from the novel The House on Mango Street by Sandra Cisneros, with additional insights obtained through library research. The study is framed through the feminist-psychology theory proposed by Karen Horney, which emphasizes that women's personalities are closely tied to their social and cultural environments. The findings reveal two key factors that shape women's personality development: family influences, which are impacted by parental support and financial difficulties, and social influences, which primarily stem from peers and the surrounding neighborhood.